Not the ones dead - Stabenow, Dana (Stabenow, Dana. Kate Shugak series, 2023)
A mid-air collision in the Alaskan wilderness between two small aircraft leaves ten people dead. Was it a bird strike, pilot error... or premeditated murder? Then an eleventh body is found in the wreckage: a man shot gangland style, twice in the chest and once in the head. In an investigation that reaches to the highest levels of government, justice may not be served, but Kate Shugak is determined that the truth will out, even at the risk of her life and the lives of those she loves most.